Culicoides (Diptera: Ceratopogonidae) from Ceará State, northeastern Brazil: Diversity, new records and bionomic approaches. (UNED Research Journal, 2019)
Introduction: little is known about the biodiversity of the genus Culicoides and the possible presence of vector species in Ceará State, Brazil. Objective: to improve the knowledge about the biodiversity and possible vectors presence in northeastern Brazil. Methods: with CDC light traps we surveyed Culicoides species in 18 municipalities from six mesoregions of Ceará State. Results: we collected 1 453 specimens (12 species). Culicoides guyanensis was the most abundant species, with 75,84% of the collected specimens. Culicoides venezuelensis is well distributed and is found in five Mesoregions. We recorded five species for the first time from Ceará State and seven from the surveyed municipalities; the presence of species with sanitary importance is discussed. Conclusion: with the addition of new species records, there are now 12 species known from Ceará State. The presence of species with medical and/or veterinary importance in the studied Mesoregions is indicative of the need of epidemiological surveillance in this state.
Keywords: biting midges; insect vectors; biodiversity; bionomy.